Magnetic compound fluid polishing of aspheric workpiece under rotating magnetic field - Ke TIAN; Huiru GUO; Yongbo WU; Zhengkai LU (Jin'gangshi yu moliao moju gongcheng, 2022)
According to the structural characteristics and the surface quality requirements of aspheric optical elements, a hemispherical head polishing head with radial magnetized permanent magnet as rotating magnetic field source is designed and manufactured on the basis of magnetic compound fluid (MCF) polishing. Firstly, through Ansoft Maxwell magnetic field simulation, the distributions of magnetic field around each magnet with different shapes, sizes and eccentricities are analyzed and compared, and the cylindrical magnet with diameter of 10.0 mm, height of 5.0 mm, eccentricity of 2.5 mm and radial magnetization is selected. Secondly, by observing and comparing the behaviors of MCF with different compositions, formula and supplies on the polishing head, the compositions of MCF polishing slurry is determined. Finally, the aspheric PMMA workpiece is polished with the prepared MCF polishing slurry and the self-made polishing head. After polishing for 15 min, the surface quality of the PMMA workpiece is significantly improved, its surface accuracy Rq is decreased from 0.703 μm to 2.433 nm, and the surface roughness Ra is reduced from 0.545 μm to 1.786 nm, indicating that the developed polishing head can realize the nano-polishing of aspheric workpiece.